Teachers Acceptance Of Mobile Learning For Teaching And Learning In Islamic Education: A Preliminary Study - Azwin Arif, Abdul Rahim; Aliff, Nawi; Mohd Isa, Hamzah (Anadolu University, 2015)
This study was conducted to investigate the perceptions of the religious teachers' readiness to use mobile phones as m-learning. The focus of the study is to examine some aspects namely;  types of handset used;  the use of mobile applications,  mobile learning activities, and;  the acceptance of mobile phones in teaching and learning. The targeted population was the religious teachers from Putrajaya, Selangor. The purposive sampling technique was used to gather data from 32 religious teachers from five secondary schools. Data were collected via questionnaires based on Likert-five-point scales. The data were tabulated, analyzed and interpreted using descriptive findings to find the frequency distribution and percentage. Research findings revealed that religious teachers are exposed to learning activities using mobile phones, and they are ready to make mobile phones as m-learning.